Vertical axis dislocation with coronal fracture of the patella: A previously unreported injury pattern. Issue 5 (October 2015) - Murphy, Lynn; Lynch-Wong, Matthew; Wong-Chung, John; Thompson, Neville
Abstract: The patella usually dislocates laterally. Less commonly, intra-articular dislocation occurs about either the vertical or horizontal axis. Patellar fractures are generally transverse with varying degrees of comminution, and less frequently vertical in the sagittal plane. We present a 9-year follow-up of a previously undescribed coronal patellar fracture associated with vertical axis dislocation of the patella. The mechanism of this severe injury is described.